Intellectual Capital, Digital Transformation, and Firm Value: A Cross-Country Analysis of Indonesian and Malaysian Banks - Aldena Selavi; Bima Cinintya Pratama; Suryo Budi Santoso; Ira Hapsari (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2025)
This study aims to examine the effect of intellectual capital components human capital (HC), structural capital (SC), and physical capital (PC) on firm value (FV), with digital transformation (DT) serve as a moderating variable. The research population consists of banking companies listed on the Indonesia Stock Exchange and Bank Negara Malaysia during the periods 2020–2023. A total of 248 observations were obtained using purposive sampling. Employing panel data regression with Stata, the results show that SC have significant positive impact on FV, PC have significant negative impact on FV, whereas HC and DT demonstrate no direct effect. However, DT significantly moderates the relationship between SC and FV, highlighting its role in strengthening organizational structures to enhance firm value in the banking sector. The findings imply that banks should prioritize digital transformation strategies that optimize structural capital such as processes, systems, and knowledge management in order to maximize firm value. Moreover, regulators and policymakers are encouraged to foster digital readiness across the industry to ensure sustainable competitiveness in the era of digital banking.